2008
DOI: 10.1017/s0007114508039986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intragastric acid stability of fat emulsions on gastric emptying, plasma lipid profile and postprandial satiety

Abstract: Fat is often included in common foods as an emulsion of dispersed oil droplets to enhance the organoleptic quality and stability. The intragastric acid stability of emulsified fat may impact on gastric emptying, satiety and plasma lipid absorption. The aim of the present study was to investigate whether, compared with an acid-unstable emulsion, an acid-stable fat emulsion would empty from the stomach more slowly, cause more rapid plasma lipid absorption and cause greater satiety. Eleven healthy male volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 49 publications
7
97
0
Order By: Relevance
“…Therefore, obese subjects can better hydrolyze fat when it is preemulsified. Moreover, fine stable emulsions were reported to be emptied faster and to cause greater release of cholecystokinin than those that broke and layered in the stomach (36,37). We thus suggest that the delay in fat absorption observed with the spread fat was due to layering in the stomach and thus to delayed emptying.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, obese subjects can better hydrolyze fat when it is preemulsified. Moreover, fine stable emulsions were reported to be emptied faster and to cause greater release of cholecystokinin than those that broke and layered in the stomach (36,37). We thus suggest that the delay in fat absorption observed with the spread fat was due to layering in the stomach and thus to delayed emptying.…”
Section: Discussionmentioning
confidence: 80%
“…The gastric emptying was linear for all emulsions while the coarse unstable emulsion (6 mm) emptied more rapidly (t 1/2 180 ± 9 min) than the fine and coarse stable ones (t 1/2 : 230 for 6 mm, 330 ± 61 min for 0.4 mm), without significant modification of the rate of energy delivery from the stomach into the duodenum up to 110 min (1.98 ± 0.22 vs. 1.67 ± 0.48 kcal/min). Additionally, no significant difference was highlighted in the plasmatic postprandial lipemia or on gallbladder contraction (Marciani et al, 2009). The stabilization of emulsion by Locust Bean Gum increased the AUC of plasmatic CCK, while this parameter was not significantly modified by droplet size changes.…”
Section: Faʃy Acids 2-mono-acyl Glycerolsmentioning
confidence: 80%
“…More CCK was released after ingestion of the acid stable meal (1095 ± 244 pmole min/L) than after acid unstable meal (531 ± 111 pmole min/L), inducing a greater gallbladder contraction and decreasing postprandial appetite (Marciani et al, 2007). In another study, authors confirmed that acid-stable meals quitted more rapidly the stomach than acid-unstable meals and once in the duodenum lipids would be hydrolyzed more rapidly because of the higher surface area available for lipase/colipase complex (Marciani et al, 2009). Authors expected also an impact on CCK release and on satiety.…”
Section: Faʃy Acids 2-mono-acyl Glycerolsmentioning
confidence: 90%
“…It has been developed at the Institute of Food Research (Norwich, UK) after intensive studies of the digestive process in healthy human volunteers using Echo-Planar Nuclear Magnetic Resonance Imaging and ileostomy patients (27)(28)(29)(30)(31)(32)(33)(34)(35). The DGM (Fig.…”
Section: Dynamic Gastric Modelmentioning
confidence: 99%